The Conspiracy of the Good: Proclus’ Theodicy qua Political Theological Paradigm - Vargas, Antonio (Political theology, 2020)
Giorgio Agamben, Dotan Leshem and Adam Kotsko have sought Christian origins of neoliberal governance. By developing a genealogical project, they have overlooked the theodicy of the Neoplatonist Proclus, which provides a more robust analogy to the neoliberal order than any Christian system. My paper develops Proclus’ theodicy as a political theological paradigm, with special attention to the divine engineering of vice by the gods in his system. In so doing, I advocate for an investigation based on analogy, rather than genealogy, and also open to a realist metaphysics. I argue that Proclus’ theodicy openly exhibits four key features of neoliberalism emphasized by Agamben, Leshem and Kotsko (governmentality, glory, expansion and demonization) and that it does so without the need for any suspicious readings of the texts or their reception. In conclusion, by closely examining an influential Hellenic Neoplatonist, I shed light on the unacknowledged polytheistic dimensions of the neoliberal world.